PJMHS 2023
DOI: 10.53350/pjmhs2023171352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oral Hygiene Practices and the Factors Influencing Selection of Tooth and Interdental-Cleaning Devises: A Cross Sectional Survey of Pakistani Adults

Abstract: Objective: The current study aimed at determining and characterizing the oral hygiene habits and behaviors of a subset of Pakistani population seeking dental care at a private hospital in Karachi. Study Design: Cross-sectional survey. Place and Duration of Study: The study was conducted in the department of Oral Medicine and Diagnosis in Dental Out-Patient-Department of Ziauddin University Karachi from January 2022 to July 2022. Methodology: A total of 530 adult males and females who visited Ziauddin Dental Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…18 The usage of interdental aids in medical students showed that most of them were aware of their usage for cleaning interproximal surfaces. [19][20]…”
Section: Discussionmentioning
confidence: 99%
“…18 The usage of interdental aids in medical students showed that most of them were aware of their usage for cleaning interproximal surfaces. [19][20]…”
Section: Discussionmentioning
confidence: 99%